Pengaruh Arus Laut terhadap Sedimentasi di Pantai Barane Kabupaten Majene - Yusman Yusman (Departemen Teknik Kelautan Universitas Hasanuddin, 2020)
Sedimentation is the deposition of rock material that has been transported by water or wind. Majene is one of the areas in Indonesia which is mostly a coastal area so it is necessary to research the sedimentation rate. The sediment rate was determined using an assembled device made of 4 m iron and a 25 cm long 2-inch pipe tied to the iron. The measurement location consists of 3 locations. The first location is located at the western end of Barane beach, the second location is in the middle and the third location is located at the eastern end of Barane Beach which is close to the river mouth. The sediment height measurement in the pipe was carried out every week for each location for 3 measurements. From the research results, the sedimentation rate at location 1 ranged from 14,788.36-23,238.85 cm3/year with average sedimentation of 18,661.5 cm3/year. The sedimentation rate for location 2 ranged from 12,675.73-21,654.38 cm3/year with an average sedimentation of 16,724.92 cm3/year. The sedimentation rate for location 3 ranges from 13732.04-16900.98 cm3/year with average sedimentation of 15,562.98 cm3/year. Ocean currents carry sediment towards the western end of the Barane coast so that the largest sedimentation rate is at the first location.